A NARRATIVE REVIEW OF ADHESIVE CAPSULITIS: INTEGRATING CONVENTIONAL AND UNANI MEDICAL PERSPECTIVES - MUBASHEERA BEGUM; HABIBULLAH V; NAZIYA TABASSUM B; MOHAMED WASEEM; MUSADDIQ AHMED; HAFSA PATEL; NUSRATH THASNEEM (The Bioscan, 2025)
Adhesive capsulitis (frozen shoulder), also termed Waja ul Mafasil in Unani medicine, affects 2–5% of the general population, rising to 11–76% in diabetics and about 11% after shoulder surgery. Women between 50–70 years and individuals with metabolic disorders show higher susceptibility. Pathophysiology in conventional medicine highlights chronic inflammation, capsular fibrosis, and cytokine activity (IL-1, IL-6, TGF-β1) leading to excess collagen deposition. Unani medicine attributes the condition to cold and dry humoral imbalances (Balgham, Sauda), paralleling molecular mechanisms of stiffness and restricted mobility. Conventional therapies such as NSAIDs, physiotherapy, and corticosteroid injections provide only partial symptom control and carry adverse effects. Unani interventions, including fomentation (takmeed), massage (dalak), dry cupping (hijamat), and herbal drugs, have shown symptomatic improvement with fewer side effects, though current data are limited to small clinical trials and observational studies. Comparative findings indicate both systems recognize inflammation and fibrosis as central drivers, though articulated differently, suggesting scope for integrative approaches. Evidence supports combining physiotherapy with Unani modalities like hijamat or herbal regimens to potentially improve functional recovery and patient satisfaction. Further large-scale randomized trials and mechanistic studies are needed to validate efficacy and establish standardized protocols.